The Impact of Special Economic Zone Policy on High Quality Economic Development in Indian Cities: Evidence from a Difference in Differences Approach - Mandira Sarma; Pralok Gupta; Priya Ramesh; Arjun Menon; Brishti Guha (Journal of Economics Business Industry, 2025)
This study aims to examine the causal impact of Special Economic Zone policy on high-quality economic development in Indian cities, with particular attention to regional heterogeneity between inland and coastal cities and the mechanisms through which the policy influences development quality. This research employs city-level panel data from 51 large and medium-sized Indian cities during 2013–2021. A Difference-in-Differences model is used to estimate the causal effect of SEZ policy on the High-Quality Economic Development Index. The index is constructed using the CRITIC weighting method across five dimensions: innovation, coordination, green development, openness, and shared prosperity. Robustness is assessed through parallel trend testing, placebo tests, alternative dependent variables, and regional heterogeneity analysis. Stepwise regression, Sobel tests, and Bootstrap tests are applied to examine the mediating roles of trade facilitation and investment liberalization. The findings show that SEZ policy significantly improves high-quality economic development in treated cities. The effect is stronger and statistically significant in inland cities, while the impact in coastal cities is insignificant. The results further reveal that SEZ policy promotes development quality by enhancing trade facilitation and investment liberalization. This study contributes to SEZ and regional development literature by shifting the focus from output growth to multidimensional development quality and by providing causal evidence from Indian city-level data. The findings suggest that policymakers should prioritize inland SEZ development, strengthen trade infrastructure, simplify regulatory procedures, improve investment access, and design region-specific SEZ policies to support balanced and sustainable urban economic transformation.